ANALYSIS OF BEGINNER INVESTOR BEHAVIOR IN CHOOSING FOREX AND STOCK INVESTMENTS: A THEORY OF PLANNED BEHAVIOR PERSPECTIVE - Rismanto Gatot; Syska Lady Sulistyowatie; Rizky Windar Amelia (Widya Dharma Journal of Business - WIJoB, 2026)
The rapid growth of beginner investors in Indonesia demonstrates a significant shift in financial market participation. However, beginner investors' investment decisions regarding forex and stock instruments are often not entirely rational and are more influenced by psychological factors, social pressures, and behavioral biases. This study aims to analyze the influence of herding behavior, risk attitude, and overoptimism on beginner investors' decisions in choosing forex or stock investments, as well as to examine the role of intention as a predictor of actual behavior according to the Theory of Planned Behavior (TPB) framework. The research employs a quantitative approach using a questionnaire survey of 140 beginner investors in Indonesia. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that all hypotheses are accepted: herding behavior (β=0.221; t=2.891; p=0.004), risk attitude (β=0.320; t=3.745; p=0.000), overoptimism (β=0.316; t=3.612; p=0.000), and intention (β=0.823; t=11.245; p=0.000) have positive and significant effects on beginner investors' decisions, with intention being the strongest predictor. This research strengthens the behavioral finance literature and extends the TPB model in the context of investment decision-making.